The Effect Of Mudharabah Financing On Increasing Income Of Mikro, Small, Medium Business (MSMES) Customer Of BPRS Bhati Sumekar Sumenep Head Office - Riskia Putri; Cahyaning Catur Utami (Cita konsultindo, 2023)
This research is to determine the effect of Mudharabah financing and the magnitude of the effect of mudharabah financing on increasing MSME income for customers of BPRS Bhakti Sumekar Sumenep Head Office. The method used is a quantitative approach to collecting primary data by distributing questionnaires to 68 respondents. And the value of the influence of Mudharabah financing with simultaneous regression results shows that the t-count value is 12.622 and the t-table is 1.668 which means that t-count > t-table, then the sig value is 0.000 and the α value is 0 .05 which means the significance value is smaller than the value of α. The results of these calculations can be concluded that the independent variable (Mudharabah financing) partially has a significant effect on the dependent variable (income), then H1 is accepted and H0 is rejected. From the results, the R Square value is 0.707 and if it is percentaged, it gets a value of 70.7%. able to indicate that the contribution to the dependent variable is 70.7% and the remaining 29.3% is found in other variables outside the regression model used.